2022
DOI: 10.1021/acs.est.2c02975
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light Activation of a Dissolved Organic Matter–TiO2 Complex Mediated via Ligand-to-Metal Charge Transfer

Abstract: Given the widespread use of TiO2, its release into aquatic systems and complexation with dissolved organic matter (DOM) are highly possible, making it important to understand how such interactions affect photocatalytic activity under visible light. Here, we show that humic acid/TiO2 complexes (HA/TiO2) exhibit photoactivity (without significant electron–hole activation) under visible light through ligand-to-metal charge transfer (LMCT). The observed visible-light activities for pollutant removal and bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…In addition, in Bi-MOFs, the Bi species acted as an electron shuttle channel for charge transfer between the ligands . This ligand-to-ligand charge transfer (LLCT) differs from the widely accepted ligand-to-metal charge transfer (LMCT) mechanism in most MOFs and can prolong the lifetime of photogenerated charge carriers, making it significantly advantageous to be applied in photo- or photoelectric catalysis. It has been reported that layered Bi-MOFs exhibited great activity and selectivity for electrochemical reduction of CO 2 to HCOOH due to the lower Gibbs free energy of the *COOH intermediates . Using surface-mounted Bi-MOFs as specific sites on the two-dimensional (2D) BiOBr support, the p band center of Bi nodes shows large downshifts and their unsaturated state is intensified, enabling the orbitals of CO 2 2p to shift downward its Fermi level, stimulating the rapid adsorption and activation of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in Bi-MOFs, the Bi species acted as an electron shuttle channel for charge transfer between the ligands . This ligand-to-ligand charge transfer (LLCT) differs from the widely accepted ligand-to-metal charge transfer (LMCT) mechanism in most MOFs and can prolong the lifetime of photogenerated charge carriers, making it significantly advantageous to be applied in photo- or photoelectric catalysis. It has been reported that layered Bi-MOFs exhibited great activity and selectivity for electrochemical reduction of CO 2 to HCOOH due to the lower Gibbs free energy of the *COOH intermediates . Using surface-mounted Bi-MOFs as specific sites on the two-dimensional (2D) BiOBr support, the p band center of Bi nodes shows large downshifts and their unsaturated state is intensified, enabling the orbitals of CO 2 2p to shift downward its Fermi level, stimulating the rapid adsorption and activation of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The modification of heterogeneous photocatalysts, such as TiO 2 , in order to shift their photoactivity spectrum from UV to visible light [ 10 , 34 , 35 , 36 , 37 ] is the key task for expanding the scope of their applications in organic synthesis, increasing selectivity and making the of use cheap and available light sources for catalyst activation possible. At present, the following modification approaches have been proposed: the immobilization of dyes (organic compounds or metal complexes) on the photocatalyst surface [ 34 , 38 , 39 , 40 , 41 ], doping with metal ions or non-metal elements [ 42 , 43 ], semiconductor coupling [ 7 , 44 , 45 , 46 , 47 , 48 , 49 ] and modification with organic molecules bearing hydroxyl or carboxyl groups [ 34 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], which demonstrate the occurrence of visible light absorption when adsorbed on the surface of a semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…To broaden the light-absorption range of TiO 2 , some modification methods such as element doping, semiconductor coupling, and dye sensitization , have been developed. Besides these popular methods, another promising approach to visible-light activation of wide band-gap TiO 2 is the formation of surface complexation to enable ligand-to-metal charge transfer (LMCT). In such an approach, organic or inorganic compounds are adsorbed and coordinated to TiO 2 , forming surface complexes and introducing new absorbance bands in the visible-light region, even though the organic or inorganic molecules themselves do not absorb visible light alone. The formed surface complexes enable the direct photoexcitation of electrons from the highest occupied molecular orbital (HOMO) of the adsorbate (ground state) to the conduction band of TiO 2 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%